Multi-Biomarker Points and Outcomes in Patients Hospitalized for Heart Failure: Insights From the China PEACE Prospective Heart Failure Study - He, Guangda; Zhang, Lihua; Huo, Xiqian; Wang, Qing; Hu, Danli; Huang, Xinghe; Ge, Jinzhuo; Wu, Yongjian; Li, Jing (Frontiers in Cardiovascular Medicine, 2022)
Objective: To quantitatively characterize the pattern of systemic impairment reflected by conventional biomarkers and assess how it relates to clinical outcomes and quality of life among patients hospitalized for heart failure (HF). Methods: Patients hospitalized for HF from 52 hospitals in China were enrolled between 2016 and 2018. They were divided into developing and validating cohorts; the developing cohort was used for calculating the weights of biomarkers and constructing the multi-biomarker panel, while the validating one was used for evaluating the relationship between multi-biomarker point and outcomes. In total, five conventional biomarkers reflecting various pathophysiological processes were included in the panel: N-terminal pro-B type natriuretic peptide, high-sensitivity troponin T, hemoglobin, albumin, and creatinine. The weights of the biomarkers were defined based on their relationship with cardiovascular death, and each patient had a multi-biomarker point ranging from 0 to 12. The primary clinical outcome was cardiovascular death, and the other clinical outcomes included rehospitalization for HF, all-cause death, and all-cause rehospitalization in 1-year. The quality of life was measured using Kansas City Cardiovascular Questionnaire. Multi-variable Cox proportional hazard models were used to assess the risks of clinical outcomes, and generalized linear models were used to evaluate the quality of life. Results: In total, 4693 patients hospitalized for HF were included in this analysis; the median (interquartile range, IQR) age was 67 (57-75) years old and 1763 (37.6%) were female. The median multi-biomarker point was 5 (IQR, 2-6). There were 18.0% of patients in low point group (< 2), 29.4% in mid-low point group (2-4), 27.8% in mid-high point group (5-6), and 24.7% in high point group (> 6). Compared with those in low point group, patients in high point group had significantly excess risk of cardiovascular death (adjusted hazard ratio: 5.69, 95% CI, 3.33-9.70). Furthermore, patients with higher point were also more prone to worse quality of life. Conclusion: Systemic impairment reflected by abnormal conventional biomarker values were common amongst patients hospitalized for HF, and had substantially cumulative adverse influence on clinical outcomes and quality of life.